الأرشفة الالکترونیة للأطروحات العلمیة فی مکتبات جامعات مکة المکرمة والمدینة المنورة : دراسة وصفیة تحلیلیة - د. عبد الرحمن غالب دبور (المجلة الدولية لعلوم المكتبات والمعلومات)
The present study aimed to analyze the current Electronic Archiving ofResearch publications. The researcher explores the actual realities of e-achievingat 3 universities of Mecca and Medina and attitudes toward electronic archivingand impediments to their implementation, in addition to the software used in earchiving of Research publications in those universities. The researcher uses thedescriptive analytical approach adopted in the analysis of the trends inuniversities of the Medina Mecca toward electronic information services based onthe electronic archiving. The researcher adopted the interview tool in addition tothe list of audit Electronic Archiving in libraries of universities in Mecca andMedina. The results show that the project of e-achieving began first in the libraryof Islamic university in the year 1426 (Hejri), we find that the Om Al Qurauniversity had started to Electronic Archiving project in the year 1427 (Hejri), andthe project of e-achieving of Taibah university began in the year 1431 (Hejri)where the project for both of these universities are library staff for each university.The study found the motive of the application of the e-archiving in the University.The evolution of the systems, including the mechanism in the area of Librariesand Information Sciences, the demand of the beneficiaries, and then to be madeavailable online through the Internet and providing time and effort. It was alsosuggested that a researcher to develop the electronic archiving of thesis in threeuniversities through supported an integrated plan to apply the electronic archivingof thesis.